The North Caucasus borderland - Yaşar, Murat. (Edinburgh)
x, 272 sayfa
Keywords: “Explores the role of the North Caucasus as the first borderland between the Ottoman and Russian Empires in the 16th centuryPresents an innovative, engaging and well-documented study of the North Caucasus and the process of the imperial rivalry that turned the region into a contested borderlandAddresses the story of imperial entanglements from multiple perspectives including folkloric and cultural sourcesAnalyses the actions of both empires and considers the motivations of the peoples caught in betweenIncludes key primary sources such as the extant Ottoman registers of important affairs (mühimme defterleri) and the Muscovite collections of diplomatic records (posol'skie knigi)From the Muscovites' annexation of the nearby Khanate of Astrakhan in 1556 to their expulsion from the region by the Ottomans and their allies in 1605, the North Caucasus was a contested borderland. This book considers the poorly understood first encounter between the Ottoman Empire and the Tsardom of Muscovy, drawing on both documentary and narrative primary sources. These Ottoman and Muscovite sources show the contrasting subject- and territory-making strategies in the early modern period. They also show how their rivalry brought about changes to the internal dynamics and strategies of the polities within the North Caucasus, shaping the region, its political structures and the lives of its peoples in the following centuries.” --